Development and Application of Outdoor Router Cost Estimation with Parametric Modelling Technique - Abel Yu Hao, Chai; Chean Hung, Lai; Fei Siang, Tay; Yi Lung, Then; Hieng Tiong, Su; Natalie Chen Yi, Lim; Chamath Kanalaka, Vithanawasam (2022)
Internet development is a challenging issue among Internet Server Providers (ISPs) and researchers due to high investment cost and unforeseen risk. The internet accessibilities of those rural areas are low and seem disconnected from the society. Rural areas unable to enjoy the benefits from high-speed Internet. Rural internet development is not prioritized because of low population density and return of investment from urban area development is more favorable. Outdoor equipment such as router, antennas and access points are the main components in Internet development. The accuracy of various cost estimation model is depending on the availability of raw data and data analysis techniques. There is no accurate model that allow ISPs to estimate the cost of outdoor routers for Wireless Fidelity (Wi-Fi) transmission. Those estimations can assist ISPs in risk management and reduce the total project cost. Therefore, this paper aimed to produce and demonstrate a suitable outdoor router cost estimation model. Friis transmission equation and link budget equation were used in this model. Suitable key parameters were selected by using P-value regression analysis. Original key parameters and calculated unique key parameters were utilized in this model to provide better performance and realistic estimated cost. This paper also demonstrated the usage of outdoor router cost estimation model under long-range and short-range wireless data transmission.